Pengaruh Budaya K3 dan Gaya Kepemimpinan terhadap Kepuasan Kerja dan Kinerja Karyawan pada Divisi Operasi Tambang Di PT Newmont Nusa Tenggara - Mulyono, Kasan (Program Doktor Ilmu Ekonomi, 2013)
There have been many studies on organizational culture. However, there have been not many studies on safety culture especially in Indonesia. Furthermore, the studies of safety culture in its relations to leadership styles, job satisfaction and employee performance have been little. This study examines the impacts of safety culture and leadership styles on employee performance with job satisfaction as an intervening variable. Primary data was obtained from the perception of employees who worked at Mining Operations Division of PT Newmont Nusa Tenggara, copper/gold mine in West Sumbawa, West Nusa Tenggara province. Data was collected through questionnaires sent to 150 employees, mostly heavy equipment operators and several field foremen. 131 were completed and returned however only 119 were valid for analysis. Statistical method used to test each hyphotesis was path analysis. The results showed that most hypothesis were confirmed. From five hypothesis, only one (H2) that had to be rejected. While four hypothesis i.e. H1, H3, H4 and H5were accepted. These results indicated that safety culture has a significant impact on job satisfaction (H1) but has no significant impact on performance (H2). Whilst leadership style has a significant impact on both job satisfaction (H3) and employee performance (H4). Finally, job satisfaction has a significant impact on employee performance (H5). Key words: Organizational culture, safety culture, leadership style, job satisfaction, performance, path analysis.